Modificação física e química do amido de quirera de arroz para aproveitamento na indústria de alimentos - Limberger, Valéria Maria (2006)
Brazil is the main producer of rice outside the Asiatic continent. During the manufacturing about 14% of broken rice are generated, this represents a great economic lost for the country s rice industry. Nevertheless, this residual product has enormous potential for utilization in food industry, as a source of starch, due to its characteristics, which can be improved through physical (extrusion) or chemical (phosphorylation) modification. The aim of the study was to evaluate the efficiency of chemical and physical modification of rice s starch of broken rice, as well as its applicability in the formulation of salgadinhos and as fat substitutes in light sausage. The physical modification was performed through extrusion and the chemical one through addition of phosphorus salts (phosphorylation). Reologic characteristics of cold water binding capacity, swelling power, solubility, syneresis and viscosity were evaluated, as well as sensoryal and chemical characteristics of salgadinhos and sausage with reduced fat content. The results demonstrated reduction in the moisture content for extruded and phosphorylated broken rice and an increase in the ash content of phosphorylated broken rice. Both phosphorylation and extrusion increased water binding capacity, swelling power, and solubility. Extruded and phosphorylated broken rice paste were stable under refrigeration, though only extruded broken rice paste was stable when submitted to freezing. Phosphorylated broken rice paste showed smaller viscosity and bigger stability when submitted to heat and the extruded one gelatinized without heating, but showed a break because of heating. The salgadinhos showed good sensoryal acceptability, in spite of the loss in appearance and color scores. The sausages that had fat replaced by phosphorylated or extrused broken rice showed sensoryal improvement when compared to low fat sausages. The changes in reologic characteristics of rice s starch of broken rice by physical through the extrusion or chemical through the phosphorylation modification makes it possible the commercial use of the former as raw material in food products, be them salgadinhos or low fat sausages.